Editorial - Ariza, J. Aleida (Universidad Pedagógica y Tecnológica de Colombia, 2013)
“We treat our location (in all its relevant senses: geographical, social,geopolitical) as the ground on which to begin our thinking. Local knowledgeis not a product constituted by the beliefs and practices of the past. Localknowledge is a process—a process of negotiating dominant discourses andengaging in an ongoing construction of relevant knowledge in the context ofour history and social practice.”1